2018
DOI: 10.1002/jum.14538
|View full text |Cite
|
Sign up to set email alerts
|

Role of Elastography in Axillary Examination of Patients With Breast Cancer

Abstract: Elastography can improve the sensitivity when disjunctively combined with conventional US for diagnosis of the axillary lymph node status. Despite the low sensitivity, the conjunctive combination of US and elastography can improve the positive predictive value on a large scale. Elastography is a useful adjuvant tool in addition to conventional US for the preoperative assessment of axillary lymph nodes in patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
5
17
1
Order By: Relevance
“…Elastography may improve the sensitivity and specificity of axilla sampling in breast cancer . Evans et al demonstrated that using shear wave elastography (SWE), nodal involvement rates ranged from 7% for tumors with a mean stiffness less than 50 kPa to 41% for tumors with a mean stiffness greater than 150 kPa, indicating that the mean stiffness on SWE is an independent predictor of axilla metastasis.…”
Section: Axillary Lymph Node Assessmentmentioning
confidence: 99%
“…Elastography may improve the sensitivity and specificity of axilla sampling in breast cancer . Evans et al demonstrated that using shear wave elastography (SWE), nodal involvement rates ranged from 7% for tumors with a mean stiffness less than 50 kPa to 41% for tumors with a mean stiffness greater than 150 kPa, indicating that the mean stiffness on SWE is an independent predictor of axilla metastasis.…”
Section: Axillary Lymph Node Assessmentmentioning
confidence: 99%
“…The common two practices are to directly evaluate the hard area ratio or to convert the hard area ratio to an elasticity score to assess the stiffness of lymph nodes. In the qualitative elastography meta-analysis, four studies directly evaluated the hard area ratio (10,12,25,26), while four others converted the hard area ratio as the elasticity score (23,24,27,28). We found that the optimal cutoff values of the hard area ratio were all 50%, and the optimal cutoff values of elasticity score were all 3.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the seven studies that reported quantitative elastography measurements were included in the quantitative elastography meta-analysis (8,(17)(18)(19)(20)(21)(22). The 11 studies that reported qualitative elastography measurements were included in the qualitative elastography meta-analysis (8)(9)(10)(11)(12)(23)(24)(25)(26)(27)(28). The inclusion and exclusion processes are summarized in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Yet, as a result of the moderate sensitivity and false-negative results, this can lead to unessential sentinel nodal sampling, which can cause related upper limb morbidities. Therefore, a need has emerged for a non-invasive tool that can accurately stage axillary lymph nodes preoperatively [3].…”
Section: Introductionmentioning
confidence: 99%
“…For breast US, it can be either strain elastography (SE) or shear wave elastography (SWE) [1]. Both exploit the fact that malignant tissues are usually stiffer than benign ones, and thus, elastography can be utilized to ameliorate the specificity of US diagnosis [3]. Strain elastography relies on the operating hand where it utilizes freehand compression to estimate elasticity of tissues [1].…”
Section: Introductionmentioning
confidence: 99%